Data-Driven Commentary on SARS-CoV-2 Infection, Vaccination, and Fertility. Issue 8 (29th June 2022) - Klipstein, Sigal; Dionne, Jodie A; Feinberg, Eve C; Kawwass, Jennifer F; Pfeifer, Samantha M; Schlegel, Peter N; Racowsky, Catherine
Abstract: A recent study by Wesselink et al. ( Am J Epidemiol . 2022;191(8):1383–1395) adds to the growing body of research finding that vaccination for coronavirus disease 2019 (COVID-19) is safe for individuals either seeking pregnancy or who are pregnant. The study's authors found no effect of COVID-19 vaccination on fecundity in a population of individuals with no known infertility who were attempting conception. The finding reinforces the messaging of the American Society for Reproductive Medicine COVID-19 Task Force, the aim of which is to provide data-driven recommendations to individuals contemplating pregnancy in the face of the COVID-19 pandemic. As safe and effective COVID-19 vaccines became available, and with an increasing number of studies showing a heightened risk of severe disease during pregnancy, an important role of the Task Force is to encourage vaccination during the preconceptual window and in early pregnancy. The Task Force supports ongoing research to address gaps in knowledge about safe and effective therapies and preventive measures for individuals contemplating pregnancy and during pregnancy. Such research will help optimize care for reproductive-age individuals in the face of current and future health crises.